Adição de cascalho de perfuração da bacia potiguar em argilas para uso em materiais cerâmicos: influência da concentração e temperatura de queima. - Medeiros, Leonardo Coutinho de (2010)
One of waste produced on large scale during the well drilling is the gravel drilling. There are techniques for the treatment of the same, but there isn t consensus on what are the best in terms of economic and environmental. One alternative for disposal of this waste and objective of this paper is the incorporation and immobilization of gravel clay matrix to assess their technological properties. The Raw Materials used were characterized by the following techniques: Chemical Analysis by X-ray fluorescence (XRF), mineralogical analysis by X-ray Diffraction (XRD), Grain Size Analysis (FA) and Thermal Analysis by Thermogravimetry (TG) and thermodiferential (DTA). After characterizing, samples were formulated in the following percentages: 0, 5, 10, 15, 25, 50, 75, 100% (weight) of gravel drilling, then the pieces were pressed, dried (110 ° C) and sintered at temperatures of 850, 950 and 1050 ° C. After sintering, samples were tested for water absorption, linear shrinkage, flexural strength, porosity, density, XRD and test color. The results concluded that the incorporation of gravel drilling is a viable possibility for solid masonry bricks and ceramic blocks manufacture at concentrations and firing temperature described here. Residue incorporation reduces an environmental problem, the cost of raw materials for manufacture of ceramic products